Galvanized steel sheet having excellent surface quality and spot weldability and method for manufacturing the same

CN116783321BActive Publication Date: 2026-10-09POHANG IRON & STEEL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180087037.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-21
Filing Date
2021-12-21
Publication Date
2026-10-09
Estimated Expiration
2041-12-21

AI Technical Summary

Technical Problem

[0005]但是,对高强度钢板的表面进行镀锌时,存在点焊性变差的问题

Benefits of technology

[0013] As described above, the present invention forms a uniform and wide-area inhibition layer between the hot-dip galvanized layer and the base steel plate, thereby inhibiting the penetration of the molten coating into microcracks during welding without the need for separate further means, and thus has the effect of improving weldability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116783321B_ABST
    Figure CN116783321B_ABST
Patent Text Reader

Abstract

The present invention relates to a high-strength hot-dip galvanized steel sheet having excellent surface quality and spot weldability and a method for manufacturing the same. According to one aspect of the present invention, the hot-dip galvanized steel sheet can include a base steel sheet; and a hot-dip galvanized layer formed on a surface of the base steel sheet, and a suppression layer composed of an Fe-Al alloy can be formed between the base steel sheet and the hot-dip galvanized layer in a proportion of 60% or more in terms of area ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a high-strength hot-dip galvanized steel sheet with excellent surface quality and spot weldability, and a method for manufacturing the same. Background Technology

[0002] Due to environmental pollution and other issues, regulations on vehicle emissions and fuel efficiency are becoming increasingly stringent. Therefore, the demand for reducing fuel consumption through lightweight automotive steel sheets is growing, leading to the development and commercialization of various high-strength steel sheets with high strength per unit thickness.

[0003] High-strength steel generally refers to steel with a strength of 490 MPa or higher, but it is not necessarily limited to this. Transformation-induced plasticity (TRIP) steel, twin-induced plasticity (TWIP) steel, dual-phase (DP) steel, and complex-phase (CP) steel can all be classified as high-strength steel.

[0004] On the other hand, to ensure corrosion resistance, automotive steel is supplied in the form of coated steel sheets with a coating on the surface. Among them, galvanized steel sheet (GI), high corrosion resistant coated steel sheet (ZM), or alloyed galvanized steel sheet (GA) have high corrosion resistance by utilizing the sacrificial corrosion protection properties of zinc, and are therefore widely used as automotive materials.

[0005] However, galvanizing high-strength steel sheets leads to poor weldability. Specifically, high-strength steel exhibits both high tensile strength and high yield strength, making it difficult to eliminate tensile stress generated during welding through plastic deformation. This increases the likelihood of microcracks forming on the surface. When welding high-strength galvanized steel sheets, the low-melting-point zinc penetrates into these microcracks, resulting in a phenomenon known as liquid metal embrittlement (LME). This leads to steel sheet failure in a fatigue environment, significantly hindering the achievement of higher strength levels. Summary of the Invention

[0006] Technical problems to be solved

[0007] According to one aspect of the present invention, a high-strength hot-dip galvanized steel sheet with excellent surface quality and spot weldability, and a method for manufacturing the same, are provided.

[0008] The technical problems addressed by this invention are not limited to those described above. Those skilled in the art can readily understand the additional technical problems of this invention based on the full text of this specification.

[0009] Technical solution

[0010] According to one aspect of the invention, a hot-dip galvanized steel sheet comprises: a base steel sheet; and a hot-dip galvanized layer formed on the surface of the base steel sheet, wherein, by area ratio, an inhibitory layer composed of an Fe-Al alloy in a proportion of more than 60% can be formed between the base steel sheet and the hot-dip galvanized layer.

[0011] A method for manufacturing hot-dip galvanized steel sheet according to another aspect of the present invention comprises the following steps: providing a steel billet; reheating the billet to a temperature of 950-1300°C; hot-rolling the reheated billet at a finishing rolling start temperature of 900-1150°C and a finishing rolling end temperature of 850-1050°C to obtain a steel sheet; coiling the steel sheet in a temperature range of 590-750°C; pickling the steel sheet at a plate throughput speed of 180-250 m / min (mpm); cold-rolling the steel sheet at a reduction rate of 35-60%; heating and recrystallizing the cold-rolled steel sheet under wet nitrogen conditions with a soaking zone temperature of 650-900°C and a dew point temperature of -10°C to +30°C, and containing 5-10% by volume H2 as the atmosphere gas; and immersing the steel sheet in a molten plating bath in an induction temperature range of 420-500°C for hot-dip galvanizing.

[0012] Beneficial effects

[0013] As described above, the present invention forms a uniform and wide-area inhibition layer between the hot-dip galvanized layer and the base steel plate, thereby inhibiting the penetration of the molten coating into microcracks during welding without the need for separate further means, and thus has the effect of improving weldability. Attached Figure Description

[0014] Figure 1 These are electron microscope photographs of the surface of the inhibition layer of a hot-dip galvanized steel sheet obtained in a specific embodiment of the present invention.

[0015] Best practice

[0016] The technical terms used herein are for describing particular embodiments only and are not intended to limit the invention. Unless the context clearly indicates otherwise, the singular forms used herein also include the plural forms.

[0017] The terms "comprising" or "including" as used in this specification are used to specifically describe a particular characteristic, region, integer, step, operation, element, and / or ingredient, and do not exclude the presence or addition of other particular characteristics, regions, integers, steps, operations, elements, ingredients, and / or groups.

[0018] Unless otherwise defined, all terms used herein, including technical and scientific terms, shall have the same meaning as commonly understood by those skilled in the art. Terms as defined in commonly used dictionaries shall be further interpreted as meaning consistent with the relevant technical literature and currently disclosed content, and shall not be construed as having an ideal or highly formal meaning unless otherwise defined.

[0019] The following is a detailed description of a high-strength hot-dip galvanized steel sheet with excellent coating quality, developed through the inventors' research, according to one aspect of the present invention. In this invention, it should be noted that, unless otherwise specified, the content of each element is expressed as a percentage by weight. Furthermore, unless otherwise specified, the proportion of crystals or structures is based on area, and unless otherwise specified, the gas content is based on volume.

[0020] The inventors of this invention focused on the fact that liquid metal embrittlement (LME) that occurs during welding is caused by the molten coating penetrating into microcracks in the base steel plate. They discovered that even if microcracks exist in the base steel plate, blocking the opportunity for the plating solution to contact the base steel plate in a molten state, or even if the contact is blocked, by hindering penetration into the interior of the microcracks, liquid metal embrittlement can be significantly suppressed, thus completing this invention.

[0021] Specifically, one aspect of the present invention aims to suppress embrittlement of liquid metal by controlling the morphology and distribution of the Fe-Al interfacial alloy layer (also known as the inhibition layer) formed in the hot-dip galvanized steel sheet of high-strength steel. The Fe-Al interfacial alloy layer has a higher melting point than the hot-dip galvanized layer, and the coating is further alloyed when the hot-dip galvanized steel sheet is heated by welding. Therefore, by increasing the melting point and viscosity of the coating, the opportunity for the plating solution to come into contact with the base steel sheet in a molten state is blocked, or even if contact occurs, the plating solution can be prevented from penetrating into microcracks due to the significantly reduced fluidity (high viscosity).

[0022] Typically, during hot-dip galvanizing, a certain degree of inhibition layer (IL) can be formed due to the diffusion reaction between the heated base steel sheet and the molten zinc bath. However, due to the high Mn and / or Si content required for high-strength steel, diffusion may be difficult to occur on the surface, and due to the characteristics of the formed inhibition layer, it is difficult for the inhibition layer to form uniformly throughout the entire interface.

[0023] In view of this, the inventors of the present invention, as Figure 1 The invention appropriately controls the shape of the inhibition layer between the hot-dip galvanized layer and the base steel plate, and limits the distribution of portions where the inhibition layer is not formed, thereby minimizing liquid metal embrittlement during welding. The preferred inhibition layer conditions of the invention are described in detail below.

[0024] The proportion of the inhibition layer: 60% or more in area

[0025] In terms of area fraction, when the inhibition layer is less than 60%, it is difficult to prevent the molten coating from contacting the base steel plate. Therefore, in one specific embodiment of the present invention, the proportion of the inhibition layer needs to be limited to 60% or more. Furthermore, to improve the effect of the inhibition layer as described above in preventing liquid metal embrittlement, in one specific embodiment of the present invention, the proportion of the inhibition layer can be 70% or more, and in another specific embodiment, the proportion of the inhibition layer can be set to 80% or more. A wider range of inhibition layer proportions is more advantageous, so there is no particular upper limit to its proportion. However, considering the morphology of the inhibition layer described below, the upper limit of the inhibition layer proportion can be set to 95% or 90%.

[0026] Morphology of the inhibition layer

[0027] In this invention, the suppression layer is not simply distributed over a large area, but can have, for example, the following characteristics: Figure 1 The particle shape is shown. At this point, it may be difficult to see that the particles are completely separated, thus making it difficult to limit the particle size, etc. However, in the accompanying drawings, when drawing a straight line along one direction, the length of the line segment overlapping the particles can be defined as the particle width. In this invention, the average width of the particles as described above is limited to 4 μm or less. By forming the fine particles as described above, even at the same area fraction of the suppression layer, the particles are densely connected, thereby preventing the molten coating from contacting the base steel plate. In particular, the particles as described above can be formed not only as a single layer but also as multiple layers. In this case, the smaller the average width of the particles, the more difficult it is for the molten coating to flow into the base steel plate side through a narrow and complex path, thus making contact with the base steel plate more difficult. A smaller average particle width is more advantageous, so it is not necessary to limit its lower limit, but as confirmed by the inventors, the lower limit of the average particle width can be 0.5 μm. In another specific embodiment of the invention, the lower limit of the average particle width can also be 1.0 μm. When the particle size is smaller than the lower limit, the interface roughness between the alloying inhibition layer and the coating is low, which cannot generate sufficient mechanical bonding force, and therefore may cause detachment.

[0028] The shape of the portion where the inhibition layer has not formed

[0029] Since the inhibition layer does not completely cover the surface of the base steel plate, there may be portions where the inhibition layer is not formed. However, even if the occupancy rate of the portions where the inhibition layer is not formed is the same, the morphology of liquid metal embrittlement may differ depending on its dispersion pattern. That is, when the portions where the inhibition layer is not formed are finely dispersed, the molten coating may have difficulty flowing into the base steel plate due to the surrounding inhibition layer, but when a small number of large-sized portions where the inhibition layer is not formed are formed, it is difficult to block the introduction of the molten coating. Therefore, in one specific embodiment of the present invention, the average equivalent circle diameter of the portions where the inhibition layer is not formed (the portions where the inhibition layer is not formed) is limited to 15 μm or less. By limiting the average size of the portions where the inhibition layer is not formed, the introduction of molten metal can be effectively blocked. Therefore, in another specific embodiment of the present invention, the average size (equivalent circle diameter) of the portions where the inhibition layer is not formed can be limited to 10 μm or less, and in another specific embodiment, the average equivalent circle diameter of the portions where the inhibition layer is not formed can be limited to 7 μm or less. Furthermore, simply limiting the average size of the unformed portions of the inhibition layer is insufficient to completely suppress the formation of large unformed portions. Therefore, in one embodiment of the invention, the number of unformed portions with an equivalent circle diameter of 20 μm or more can be limited to one or less; in another embodiment, the number of unformed portions with an equivalent circle diameter of 15 μm or more can be limited to one or less; and in yet another embodiment, the number of unformed portions with an equivalent circle diameter of 10 μm or more can be limited to two or less. When a large number of large unformed portions of the inhibition layer are present, the mechanical bonding between the inhibition layer and the zinc plating is insufficient, which may lead to plating peeling. Additionally, the area of ​​liquid zinc that can contact the substrate iron increases during spot welding, potentially leading to the development of liquid embrittlement cracks.

[0030] In this invention, the inhibition layer is analyzed using the following method. First, for the surface of a hot-dip galvanized steel sheet, the unalloyed coating (typically composed of Zn in the eta phase, but not necessarily limited to this) is dissolved with a dichromic acid solution (CrO3+HNO3+ZnSO4+H2O). The obtained surface is then neutralized, washed, and cleaned, exposing only the inhibition layer on the surface. Next, to analyze the occupancy (area ratio) of the inhibition layer, in photographs analyzing Al distribution at 500x magnification using EPMA, areas with a concentration (CPS) of 10% or more of the maximum Al concentration (measured by CPS) are considered to contain the Al inhibition layer, and their area ratio can be used as the occupancy of the inhibition layer. Similarly, the shape of the portions without the inhibition layer can also be obtained using the same method.

[0031] In addition, the width of the suppression layer particles can be obtained by the following method: when drawing lines in SEM images at the same magnification, the area where the line and the suppression layer overlap is regarded as one width of the suppression layer, and the average of these widths is obtained.

[0032] In one specific embodiment of the present invention, the shape and occupancy of the inhibition layer and the shape of the unformed portion of the inhibition layer can utilize values ​​obtained at the center of the steel plate in the width direction. However, it is not necessarily limited to this location; for example, spot weldability is often problematic at the edge in the width direction, so values ​​obtained at the edge in the width direction can also be used. Here, the edge in the width direction refers to the two ends of a section cut along the width direction of the steel plate, but when the integrity of the specimen is problematic, such as contamination occurring at the aforementioned location, it can refer to a position 1 mm inward along the width direction from the endpoint.

[0033] The type of steel plate targeted in this invention is not limited as long as it is a high-strength steel plate with a strength of 780 MPa or higher. However, the steel plate targeted in this invention may have a composition comprising, by weight, 0.05-1.5% C, 2.0% or less Si, 1.0-10% Mn, 3% or less acid-soluble aluminum (S-Al), 2.5% or less Cr, 1% or less Mo, 0.005% or less B, 0.2% or less Nb, 0.2% or less Ti, 0.2% or less V, 0.2% or less Sb+Sn+Bi, 0.1% or less Sb+Sn+Bi, and 0.01% or less N, but is not necessarily limited to this. The remaining components are iron and other impurities. In addition, it is not excluded that elements not listed above but which may be included in steel may be further included in the range of 1.0% or less in total. Unless otherwise specified, the content of each component element in this invention is expressed on a weight basis. The above composition refers to the bulk composition of the steel plate, that is, the composition at 1 / 4 of the thickness of the steel plate (hereinafter the same).

[0034] However, in some specific embodiments of the present invention, TRIP steel, DP steel, and CP steel can be used as the high-strength steel plate. Each steel can have the following composition.

[0035] Steel composition 1: comprising C: 0.05-0.30% (preferably 0.10-0.25%), Si: 0.5-2.5% (preferably 1.0-1.8%), Mn: 1.5-4.0% (preferably 2.0-3.0%), S-Al: less than 1.0%, Cr: less than 2.0% (preferably less than 1.0%), Mo: less than 0.2% (preferably less than 0.1%), B: less than 0.005% (preferably less than 0.004%), Nb: less than 0.1% (preferably less than 0.05%), Ti: less than 0.1% (preferably 0.001-0.05%), Sb+Sn+Bi: less than 0.05%, N: less than 0.01%, balance Fe, and unavoidable impurities. Depending on the circumstances, elements not listed above but permitted in the steel may be further included in the range of less than 1.0% in total.

[0036] While not necessarily limited to this, the steel used as component 1 may include TRIP steel or XF steel, and may each have a tensile strength of 900 MPa or more.

[0037] Steel composition 2: comprising C: 0.05-0.30% (preferably 0.10-0.2%), Si: less than 0.5% (preferably less than 0.3%), Mn: 4.0-10.0% (preferably 5.0-9.0%), S-Al: less than 0.05% (preferably 0.001-0.04%), Cr: less than 2.0% (preferably less than 1.0%), Mo: less than 0.5% (preferably 0.1-0.35%), B: less than 0.005% (preferably less than 0.004%), Nb: less than 0.1% (preferably less than 0.05%), Ti: less than 0.15% (preferably 0.001-0.1%), Sb+Sn+Bi: less than 0.05%, N: less than 0.01%, balance Fe, and unavoidable impurities. Depending on the circumstances, elements not listed above but permitted in the steel may be further included in the range of less than 1.0% in total.

[0038] While not necessarily limited to this, examples of steels used in steel composition 2 include TRIP steel and XF steel, and they can have tensile strengths of 1000 MPa or more.

[0039] According to one embodiment of the present invention, the surface of the steel plate may include one or more coatings, which may be zinc-based coatings including galvanized (GI) or zinc-magnesium (ZM). In the present invention, by appropriately controlling the oxygen concentration of the surface layer as described above, the problem of liquid metal embrittlement during spot welding can be suppressed even when formed on the surface of a zinc-based coated steel plate.

[0040] Furthermore, the coating thickness of the zinc-based coating can be 30-70 g / m². 2 When the coating thickness is too low, sufficient corrosion resistance is difficult to achieve. On the other hand, when the coating thickness is too high, it may lead to increased manufacturing costs and embrittlement of the liquid metal. Therefore, the coating thickness is controlled within the aforementioned range. A more preferred coating thickness range is 40-60 g / m². 2 .

[0041] The following describes a specific embodiment of manufacturing the steel plate of the present invention. However, it should be noted that the steel plate of the present invention is not necessarily manufactured through the specific embodiment described below; the specific embodiment described below is a preferred method for manufacturing the steel plate of the present invention.

[0042] First, hot-rolled steel sheets can be manufactured through the following process: a steel billet having the above composition is reheated, hot-rolled by roughing and finishing rolling, and then cooled by the run-out table (ROT) before being coiled. No particular restrictions are placed on the hot rolling conditions such as ROT cooling; however, in one specific embodiment of the invention, the slab reheating temperature, finishing rolling start temperature, finishing rolling end temperature, and coiling temperature can be limited as follows.

[0043] Slab reheating temperature: 950-1300℃

[0044] Reheating of the slab is performed to ensure rollability by heating the material before hot rolling. During the reheating process, the surface layer of the slab combines with oxygen in the furnace to form an oxide scale. When the heating temperature is sufficiently high, the composition of the oxides on the surface and inside of the steel sheet can be controlled within an appropriate range due to the interaction with the processes described below. However, when the heating temperature is too high, excessive grain growth may occur, and the material quality of the steel sheet may deteriorate. Therefore, the slab is reheated to the aforementioned temperature range.

[0045] Finishing rolling starting temperature: 900-1150℃

[0046] When the finishing rolling starting temperature is too high, the surface hot-rolled oxide scale becomes excessively developed, which may increase the amount of surface defects caused by the oxide scale in the final product. Therefore, the upper limit of the finishing rolling starting temperature is limited to 1150°C. In addition, when the finishing rolling starting temperature is below 900°C, the rigidity of the bar increases due to the decrease in temperature, which may significantly reduce the hot rollability. Therefore, the finishing rolling starting temperature can be limited to the above range.

[0047] Finishing rolling temperature: 850-1050℃

[0048] When the finishing rolling termination temperature exceeds 1050℃, the oxide scale removed during the finishing rolling process will re-form excessively on the surface, leading to an increase in the amount of surface defects. When the finishing rolling termination temperature is below 850℃, the hot rollability decreases. Therefore, the finishing rolling termination temperature can be limited to the above range.

[0049] Winding temperature: 590-750℃

[0050] Hot-rolled steel sheets are stored in coils, which undergo a slow cooling process. This process removes oxidizing elements from the surface of the steel sheet. However, if the coiling temperature is too low, the coil is slowly cooled below the required temperature for removing these oxidizing elements, making it difficult to achieve sufficient results. Furthermore, if the coiling temperature is too high, it may be difficult to ensure the tensile strength and other material properties of the steel sheet, and due to excessive oxidation inside the hot-rolled coil, coating quality, such as adhesion, may deteriorate.

[0051] Heating of the edges of hot-rolled coils: at 600-800℃ for 5-24 hours.

[0052] In one specific embodiment of the present invention, in order to increase the average Mn / Si value of the surface oxides at the edge and decrease the average Mn / Si value of the internal oxides at a depth of 100 nm or more in the steel sheet, the edge of the hot-rolled coil can be heated. Heating the edge of the hot-rolled coil refers to heating both ends of the coil in the width direction, i.e., the edge portion. By heating the edge portion, it is first heated to a temperature suitable for oxidation. That is, the interior of the coil remains at a high temperature, but the edge portion is cooled relatively quickly, thus the time the edge portion remains at a temperature suitable for internal oxidation is relatively short. Therefore, compared to the center portion in the width direction, the removal of oxidizing elements in the edge portion is less active. Heating the edge portion can be used as a method for removing oxidizing elements from the edge portion.

[0053] That is, when heating the edge portion, unlike the cooling process after coiling, the edge portion is heated first, thereby maintaining the temperature of the edge portion in the width direction at a temperature suitable for internal oxidation, resulting in an increase in the thickness of the internal oxide layer at the edge portion. Therefore, the heating temperature of the edge portion needs to be above 600°C (based on the temperature of the steel plate edge). However, when the temperature is too high, the tensile strength of the steel plate decreases, excessive oxide scale is formed at the edge portion during heating, or a porous, highly oxidized oxide scale (ferric oxide) is formed, which may worsen the surface condition after pickling. Therefore, the heating temperature of the edge portion can be below 800°C. More preferably, the heating temperature of the edge portion is 600-750°C. According to a specific embodiment of the invention, the heating of the edge portion can be carried out in a heat treatment furnace.

[0054] Furthermore, to eliminate the unevenness in the average Mn / Si value of the surface oxides between the edge and center portions in the width direction that occurs during winding, and the unevenness in the average Mn / Si value of the internal oxides with a depth of 100 nm or more within the steel sheet, the heating time for the edge portion needs to be 5 hours or more. However, if the heating time for the edge portion is too long, the tensile strength of the steel sheet decreases, excessive oxide scale forms, or conversely, the average Mn / Si value of the surface oxides at the edge portion becomes too high, or the average Mn / Si value of the internal oxides may become too low. Therefore, the heating time for the edge portion can be 24 hours or less.

[0055] According to one specific embodiment of the present invention, the heating of the edge portion can be achieved by adjusting the air-fuel ratio for combustion heating. That is, the oxygen fraction in the atmosphere can be changed by adjusting the air-fuel ratio. When the oxygen partial pressure is high, excessive highly oxidizing ferric oxide (Fe₂O₃) and fayalite (Fe₂SiO₄) as an interface oxide are produced, and the coating surface quality may deteriorate. Conversely, when the oxygen partial pressure is low, it becomes unfavorable to ensure a proper heating temperature. This is not necessarily a limitation, but in one specific embodiment of the invention, the air-fuel ratio can be adjusted to control a nitrogen atmosphere containing 1-2% oxygen. Those skilled in the art can easily control the oxygen fraction by adjusting the air-fuel ratio, and therefore, this will not be described separately.

[0056] Pickling: Performed at a plate throughput speed of 180-250 m / min.

[0057] The hot-rolled steel sheet, after the above process, is added to a hydrochloric acid bath for pickling to remove the hot-rolled oxide scale. The hydrochloric acid concentration in the bath during pickling is in the range of 10-30% by volume, and the plate throughput speed is 180-250 m / min. When the pickling speed exceeds 250 m / min, the oxide scale on the surface of the hot-rolled steel sheet may not be completely removed. When the pickling speed is below 180 m / min, the surface layer of the base iron may be corroded by the hydrochloric acid. Therefore, the pickling is carried out at a plate throughput speed of 180 m / min or higher.

[0058] Cold rolling: reduction rate 35-60%

[0059] After pickling, cold rolling is performed. The cold rolling reduction rate is in the range of 35-60%. When the cold rolling reduction rate is less than 35%, although there are no particular problems, it may be difficult to fully control the microstructure due to insufficient recrystallization driving force during annealing. When the cold rolling reduction rate exceeds 60%, it is difficult to achieve an appropriate average Mn / Si value for the surface oxides after annealing and an average Mn / Si value for the internal oxides of the steel sheet with a depth of more than 100 nm.

[0060] Following the aforementioned cold rolling process, an annealing process can be performed on the steel sheet. During the annealing process, the average Mn / Si value of the oxides on the surface of the steel sheet and the average Mn / Si value of the oxides in the interior of the steel sheet with a depth of 100 nm or more may change significantly. Therefore, in a specific embodiment of the present invention, the annealing process can be controlled under the condition of appropriately controlling the average Mn / Si value of the oxides on the surface and the average Mn / Si value of the oxides in the interior of the steel sheet with a depth of 100 nm or more. The sheet throughput speed and the dew point in the annealing furnace can be controlled under the following conditions.

[0061] Through speed: 40-130 m / min

[0062] To ensure sufficient productivity, the cold-rolled steel sheet needs to be passed through at a speed of 40 meters per minute or more. However, excessively high speeds may be detrimental to material quality; therefore, in one embodiment of the invention, the upper limit of the passing speed can be set to 130 meters per minute.

[0063] Temperature and dew point control in the soaking zone of the annealing furnace: maintained within the range of -10℃ to 30℃ at 650-900℃.

[0064] To control the Mn / Si ratio in the oxides of both the internal and surface layers within an appropriate range, it is advantageous to control the dew point in the soaking zone of the annealing furnace. When the dew point is too low, surface oxidation occurs instead of internal oxidation, and oxides such as Si or Mn may form on the surface. These oxides have an adverse effect on the plating. Therefore, it is necessary to control the dew point to above -10°C. On the other hand, when the dew point is too high, Fe oxidation may occur, so it is necessary to control the dew point to below 30°C. As mentioned above, the temperature used to control the dew point can be above 650°C to achieve a sufficient internal oxidation effect. However, when the temperature is too high, surface oxides such as Si form, which not only hinder oxygen diffusion to the interior but also generate excessive austenite during heating in the soaking zone, reducing the carbon diffusion rate. Therefore, the level of internal oxidation may decrease, and excessive austenite growth in the soaking zone may lead to material softening. Furthermore, it may increase the load on the annealing furnace, causing problems such as shortened equipment life and increased process costs. Therefore, the temperature for controlling the dew point can be below 900°C.

[0065] At this point, the dew point can be adjusted by adding wet nitrogen (N2+H2O) containing water vapor into the annealing furnace.

[0066] Hydrogen concentration in the annealing furnace (soaking zone): 5-10% by volume

[0067] The atmosphere inside the annealing furnace is maintained by adding 5-10% by volume of hydrogen to the nitrogen. When the hydrogen concentration inside the annealing furnace is less than 5% by volume, excessive surface oxides are formed due to the reduced reducing power, resulting in poor surface quality and coating adhesion, and reduced resistance to LME (Liquid Metal Electrode Regulator). While no particular problems arise at higher hydrogen concentrations, the increased cost due to increased hydrogen usage and the risk of furnace explosion caused by higher hydrogen concentrations necessitate limiting the hydrogen concentration.

[0068] Introducing temperature of the steel sheet for plating bath: 420-500℃

[0069] When the temperature of the steel sheet introduced into the plating bath is too low, the wettability at the interface between the steel sheet and the liquid zinc cannot be adequately ensured; therefore, it should be maintained above 420℃. When the temperature of the steel sheet introduced into the plating bath is too high, the steel sheet reacts excessively with the liquid zinc, generating a ζ phase at the interface, which is an Fe-Zn alloy phase. This leads to reduced coating adhesion and excessive leaching of Fe from the steel sheet, resulting in scum formation within the plating bath.

[0070] To ensure the wettability of the coating and the fluidity of the plating bath, the Al concentration in the plating bath should be maintained at an appropriate level. In the case of GI, Al should be controlled at 0.2-0.25% by weight; in the case of ZM, Al should be controlled at 0.7-13.2% by weight, and Mg should be controlled at 0.7-5.7% by weight and maintained at appropriate levels. This ensures that the formation of dross in the plating bath is kept at an appropriate level and that the quality and performance of the coated surface are guaranteed. There are no particular limitations on the coating adhesion amount in this invention, but it can be appropriately adjusted according to the quality requirements of the customer. Detailed Implementation

[0071] The present invention will now be described in more detail through embodiments. However, it should be noted that the following embodiments are merely illustrative of the invention and are not intended to limit the scope of the invention. This is because the scope of the invention is determined by the contents of the claims and the contents reasonably deduced therefrom.

[0072] (Example)

[0073] A steel billet with the composition listed in Table 1 (the remaining components not listed in the table are Fe and unavoidably contained impurities. In addition, B and N in the table are expressed in ppm, and the remaining components are expressed in % by weight) is reheated to 1213°C, hot-rolled with the finishing rolling start temperature and finishing rolling end temperature set at 1117°C and 972°C respectively, and then the hot-rolled coil is heated at the edges for 8 hours in a nitrogen atmosphere with oxygen concentration of less than 1.5 vol%. Then it is pickled in a hydrochloric acid bath with an average hydrochloric acid concentration of 15 vol% at a speed of 180 m / min and cold-rolled. Finally, the obtained cold-rolled steel sheet is annealed in an annealing furnace in a soaking zone in an atmosphere with hydrogen concentration of 8 vol% and the balance being nitrogen. After annealing, GI is immersed in a plating bath containing 0.24 wt% Al, and ZM is immersed in a zinc-based plating bath containing 1.75 wt% Al and 1.55 wt% Mg for hot-dip galvanizing. The adhesion amount is then adjusted by an air knife and cooled to obtain hot-dip galvanized steel sheet.

[0074] In all embodiments, the introduction temperature of the steel sheet into the hot-dip galvanizing bath is set to 475°C. Other conditions for each embodiment are described in Table 2.

[0075] [Table 1]

[0076] A 0.245 0.245 7.214 0.0027 0 0 15 0.017 0.019 0 0 0 B 0.212 1.548 2.225 0.0052 0 0.0024 17 0.024 0.014 0 0.0045 0 C 0.214 0.02 6.875 0.0025 0 0 11 0 0.054 0 0 0 D 0.147 0.04 15.57 0.0026 0 0 21 0.0021 0.045 0.024 0 0 E 0.175 1.542 2.685 0.0054 0.457 0.0475 11 0.05 0.032 0 0 0.01 F 0.156 2.954 2.654 0.0034 0.447 0.017 17 0.0045 0.021 0 0 0 G 0.195 1.425 2.654 0.0024 0.354 0.0021 14 0 0.021 0.011 0 0

[0077] [Table 2]

[0078]

[0079]

[0080] The properties of hot-dip galvanized steel sheets manufactured through the above process were measured, and the occurrence of liquid metal embrittlement (LME) during spot welding was observed. The results are shown in Table 3. Unless otherwise specified, the test results shown in Table 3 were measured using samples collected 1 mm from the edge of the steel sheet. When the sample size was large, samples of a specified size were measured starting from 1 mm from the edge. Specifically, spot welding was performed by cutting the steel sheet along its width and along the edges of each cut. Two spot welding currents were applied, followed by a hold time of one cycle. Spot welding was performed in two three-layer configurations. The evaluation material was stacked and spot welded in the order of evaluation material-evaluation material-GA980DP1.4t material. During spot welding, a new electrode was welded to a soft material 15 times, after which the electrode was worn down, and the upper limit current at which spatter occurred was measured using the material to be spot welded. After measuring the upper limit current, eight spot welds were performed at currents 0.5 kA and 1.0 kA lower than the upper limit current, at each welding current. The cross-section of the spot weld was then precision machined using electrical discharge machining, fixed with epoxy resin (epoxy mounting), and ground. Crack lengths were measured using an optical microscope. When observing with the optical microscope, the magnification was set to 100x. If no cracks were found at this magnification, it was determined that liquid metal embrittlement had not occurred. If cracks were found, their lengths were measured using image analysis software. A good result was considered achieved when B-type cracks at the shoulder of the spot weld were less than 100 μm and no C-type cracks were observed.

[0081] For the proportion of the inhibition layer (IL) coated on the steel plate surface (mainly composed of Zn-eta phase), the coating was dissolved with dichromic acid solution (CrO3+HNO3+ZnSO4+H2O), then the surface was neutralized, washed, and cleaned. Then, in images of Al distribution at 500x magnification using EPMA analysis of at least three locations, the area with the highest Al concentration (CPS reference) of 10% or more was considered the area where the inhibition layer existed. The proportion of this area was calculated using image analysis software to obtain the average area percentage. When this value was 60% or more, it was considered good. The size of the unformed inhibition layer was also distinguished using the same method. In all the following examples, there were no unformed inhibition layers with a size of 15 μm. In all examples, it was confirmed that the average width of the particles constituting the inhibition layer corresponded to the range of 0.5-4 μm.

[0082] Tensile strength was measured by manufacturing a sample in the C direction according to JIS-5 standard and performing a tensile test. The degree of alloying and the amount of plating were measured using a wet dissolution method with hydrochloric acid solution.

[0083] To check for sealant adhesion, after attaching the automotive structure to the coated surface with D-type adhesive, bend the steel plate 90 degrees and check whether the coating has peeled off.

[0084] The surface quality is confirmed by visually inspecting for defects such as uncoated steel plates. If defects are observed during visual inspection, the plate is deemed defective.

[0085] [Table 3]

[0086]

[0087] In Invention Examples 1, 2, 3, 4, 5, 6, 7, and 8, the steel composition and manufacturing method satisfy the scope of the present invention, thereby achieving good tensile strength, plating quality, plating adhesion, and spot weld LME crack length.

[0088] In Comparative Examples 1 and 8, although the manufacturing methods met the scope of the present invention, the steel composition exceeded the scope of the present invention. In Comparative Examples 1 and 8, Mn and Si respectively exceeded the scope of the present invention, and the area ratio of the inhibition layer of the coated steel sheet did not meet the benchmark when the dew point of the annealing furnace rose. Due to the excessive Si and Mn content, excessive surface oxides were formed during the annealing process. Therefore, a sufficient decarburization layer could not be formed, and an alloying inhibition layer could not be sufficiently formed at the interface between the coating and the base iron. As a result, LME cracks did not meet the benchmark, uncoated surfaces occurred, leading to poor surface quality, and poor coating adhesion due to SBT peeling.

[0089] In Comparative Examples 6 and 11, the coiling temperature during the hot rolling process did not meet the range proposed in this invention. In Comparative Example 6, the hot rolling coiling temperature was below the range proposed in this invention. Due to insufficient internal oxidation during hot rolling, the area ratio of the inhibition layer of the coated steel sheet was less than 60% of the area, thus failing to meet the LME crack criterion. In Comparative Example 11, manufacturing was carried out at a hot rolling coiling temperature exceeding that proposed in this invention. Due to sufficient internal oxidation generated during hot rolling, the LME characteristics were good. However, due to the excessive hot-rolled oxide scale generated, the oxide scale could not be completely removed during pickling, resulting in uncoated material and poor surface quality. Furthermore, due to the excessively high hot rolling coiling temperature, the hot-rolled material softened and could not be restored after annealing, resulting in poor material quality.

[0090] Comparative Examples 13 and 14 represent cases where the heat treatment temperature in the edge heat treatment process does not meet the range proposed in this invention. In Comparative Example 13, because the heating temperature of the heat treatment furnace exceeded the range proposed in this invention, excessive interfacial oxide scale and highly oxidizing oxide scale were formed in the edge. The oxide scale could not be completely removed after pickling and remained as Si-based oxides, resulting in poor surface quality. Furthermore, due to overheating of the edge, softening occurred, thus failing to meet the tensile strength requirement. Additionally, because Si-based oxides are not readily reactive in high dew point atmospheres, the LME resistance did not meet the benchmark. In Comparative Example 14, because the edge heating temperature was below the range proposed in this invention, an internal oxide layer could not be sufficiently formed, and a sufficient inhibition layer could not be formed during the plating process. Therefore, the plating surface quality and sealant adhesion were poor, and the LME resistance was not met.

[0091] Comparative Example 4 illustrates a case where the furnace dew point during annealing is below the range proposed in this invention. In the hot rolling heating process, even if a sufficient internal oxide layer is formed across the entire width, the dew point is insufficient during the annealing process after cold rolling, preventing adequate internal oxidation. Consequently, the area ratio of the inhibition layer on the coated steel sheet is less than 60% and a sufficient level of decarburization cannot be achieved, resulting in poor LME crack length in spot welds. Due to its low dew point, GI material cannot undergo sufficient internal oxidation, producing excessive surface oxides, thus resulting in poor surface quality.

[0092] In Comparative Example 2, the dew point range in the annealing furnace exceeded the range proposed in this invention. While the dew point increased excessively, sufficient internal oxidation occurred, thus the LME met the benchmark. However, due to excessive internal oxidation, the material deteriorated, and therefore the benchmark was not met.

[0093] Comparative Examples 3 and 7 were manufactured under conditions where the steel sheet passing speed during annealing was higher than the range proposed in this invention. Due to insufficient time for the decarburization reaction between water vapor and the steel sheet in the annealing path, the internal oxidation of the surface layer of the annealed steel sheet was inadequate. Therefore, the area ratio of the inhibition layer on the coated steel sheet was less than 60% and the LME crack evaluation of the spot weld exceeded the benchmark and was deemed unsatisfactory.

[0094] In Comparative Example 12, the temperature in the soaking zone of the annealing furnace exceeded the range proposed in this invention. As the annealing temperature became excessively high, the external oxidation increased, preventing the formation of sufficient internal oxidation. Consequently, the area ratio of the inhibition layer on the coated steel sheet was less than 60% of the area, and the LME cracks did not meet the benchmark, resulting in poor spot weldability. Furthermore, excessive austenite formation and growth occurred in the soaking zone, causing the material to fail to meet the benchmark and thus be defective.

[0095] Comparative Example 10 illustrates a case where the soaking zone temperature in the annealing furnace is lower than the range proposed in this invention. Due to the low annealing temperature, the oxidation reaction between water vapor and the steel plate is insufficient, preventing adequate internal oxidation. Consequently, the area ratio of the inhibition layer on the coated steel plate is less than 60% of the area, and the LME crack does not meet the benchmark, resulting in poor spot weldability. Furthermore, insufficient recrystallization occurs during annealing, preventing the formation of the desired fine microstructure, thus the material does not meet the benchmark and is defective.

[0096] Comparative Example 5 illustrates a case where the steel sheet passed through at a speed lower than that proposed in this invention during annealing. While sufficient reaction time with the water vapor in the annealing furnace was ensured to adequately form the internal oxide layer, excessive grain growth resulted in failure to meet material standards.

[0097] In Comparative Example 9, manufacturing was carried out with a cold rolling reduction exceeding the benchmark proposed in this invention. The internal oxide layer formed during hot rolling became thinner due to excessive cold rolling, resulting in insufficient internal oxidation. Consequently, the area ratio of the inhibition layer of the coated steel sheet was less than 60% and the LME cracks did not meet the benchmark, thus rendering the process unsatisfactory.

[0098] Therefore, the advantageous effects of the present invention can be confirmed.

Claims

1. A hot-dip galvanized steel sheet, comprising: Foundation steel plate; as well as A hot-dip galvanized layer is formed on the surface of the base steel plate. By area ratio, an inhibitory layer consisting of more than 60% Fe-Al alloy is formed between the base steel plate and the hot-dip galvanized layer. The average width of the particles constituting the inhibition layer is less than 4 μm. The average equivalent circle diameter of the portion where the inhibition layer is not formed is less than 15 μm. The average width of the particles is defined as the average width of the particle obtained by drawing a straight line along one direction in a top-view image of the suppression layer, with the length of the line segment overlapping the particles set as the width of the particles.

2. The hot-dip galvanized steel sheet according to claim 1, wherein, The inhibition layer is formed with an area ratio of more than 70%.

3. The hot-dip galvanized steel sheet according to claim 1, wherein, The average width of the particles constituting the inhibition layer is 0.5 μm or more.

4. The hot-dip galvanized steel sheet according to claim 1, wherein, The base steel plate has a composition comprising C: 0.05-1.5%, Si: less than 2.0%, Mn: 1.0-10%, acid-soluble aluminum (S-Al): less than 3%, Cr: less than 2.5%, Mo: less than 1%, B: less than 0.005%, Nb: less than 0.2%, Ti: less than 0.2%, V: less than 0.2%, Sb+Sn+Bi: less than 0.1%, and N: less than 0.01%.

5. A method for manufacturing the hot-dip galvanized steel sheet of claim 1, comprising the following steps: Provide steel billets; The slab is then reheated to a temperature of 950-1300℃. The reheated slab is hot-rolled at a finishing rolling start temperature of 900-1150°C and a finishing rolling end temperature of 850-1050°C to obtain a steel plate. The steel plate is coiled within a temperature range of 590-750℃; The steel plate is pickled at a throughput speed of 180-250 meters per minute; The steel plate is cold-rolled with a reduction rate of 35-60%; The cold-rolled steel sheet is heated and recrystallized under wet nitrogen conditions with a soaking zone temperature of 650-900°C and a dew point temperature of -10°C to +30°C, and the atmosphere gas containing 5-10% by volume H2; and The steel plate is immersed in a molten plating bath for hot-dip plating within an induction temperature range of 420-500°C.

6. The method according to claim 5, wherein, The molten plating bath contains 0.2-0.25% by weight of Al.

7. The method according to claim 5, wherein, The molten plating bath contains 0.7-13.2% by weight of Al and 0.7-5.7% by weight of Mg.

8. The method according to any one of claims 5 to 7, wherein, The plate throughput speed during recrystallization annealing is 40-130 m / min.

9. The method according to any one of claims 5 to 7, wherein, The edges of the coiled steel plate are heated at 600-800℃ for 5-24 hours.

Citation Information

Patent Citations

  • KR1017260900000B1

  • KR20200076796A